2016
DOI: 10.1155/2016/9705287
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Resistance Training Methods with and without Protein Supplementation to Fight Cardiometabolic Risk in Middle-Aged Males: A Randomized Controlled Trial

Abstract: Time-effective protocols may potentially increase people's compliance with exercise. The purpose of this paper was to compare the relative effects of 16 weeks of high intensity (resistance) training (HIT) with and without protein supplementation (HIT&P) and HVHIT (high volume/high intensity training) versus a nontraining control group on cardiometabolic risk factors. One hundred and twenty untrained males 30–50 years old were randomly assigned to 3 subgroups: (a) a HIT group; (b) a HIT&P group, and (c) a waiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Unfortunately, the sample size ( n ≤10/subgroup) of this study may have been too low to generate adequate power to clearly address this issue. However, generating a more adequate statistical power, Kemmler et al30 demonstrated that 16 weeks of high-intensity resistance exercise with or without additional proteins (total protein intake: ≥1.5 g/kg body mass/day) did not result in significant group differences with respect to improvements of the MetS in a comparable male cohort. In parallel, after 6 months of a predominantly resistance-type protocol conducted with moderate volume and high intensity (80% of 1 repetition maximum), Weinheimer et al31 did not demonstrate a significant additional effect of whey protein (20, 40, or 60 g/day) on the MetS in middle-aged overweight to obese persons.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the sample size ( n ≤10/subgroup) of this study may have been too low to generate adequate power to clearly address this issue. However, generating a more adequate statistical power, Kemmler et al30 demonstrated that 16 weeks of high-intensity resistance exercise with or without additional proteins (total protein intake: ≥1.5 g/kg body mass/day) did not result in significant group differences with respect to improvements of the MetS in a comparable male cohort. In parallel, after 6 months of a predominantly resistance-type protocol conducted with moderate volume and high intensity (80% of 1 repetition maximum), Weinheimer et al31 did not demonstrate a significant additional effect of whey protein (20, 40, or 60 g/day) on the MetS in middle-aged overweight to obese persons.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a 22-week randomized controlled exercise trial with a parallel group design, focusing on the effect of high intensity, single set resistance exercise protocols (HI(R)T) on functional and morphologic cardiac parameters in middle-aged (30–50 years old) untrained males compared to sedentary controls. Details of the whole PUSH trial have been described before [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, 120 participants were randomly assigned to a HI(R)T- (n = 40), control- (n = 40), and HI(R)T & protein supplementation-group (n = 40). The latter one was investigated by the collaborative institute and did not receive cardiac MRI [ 16 ]. All subjects of HI(R)T- and control-group received cardiac MRI before and after the intervention period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations